Activation of an AP1-Like Transcription Factor of the Maize Pathogen Cochliobolus heterostrophus in Response to Oxidative Stress and Plant Signals - Lev, Sophie (American Society for Microbiology, 2005)
Redox sensing is a ubiquitous mechanism regulating cellular activity. Fungal pathogens face reactive oxygen species produced by the host plant's oxidative burst in addition to endogenous reactive oxygen species produced during aerobic metabolism. An array of preformed and induced detoxifying enzymes, including superoxide dismutase, catalases, and peroxidases, could allow fungi to infect plants despite the oxidative burst. We isolated a gene (CHAP1) encoding a redox-regulated transcription factor in Cochliobolus heterostrophus, a fungal pathogen of maize. CHAP1 is a bZIP protein that possesses two cysteine-rich domains structurally and functionally related to Saccharomyces cerevisiae YAP1. Deletion of CHAP1 in C. heterostrophus resulted in decreased resistance to oxidative stress caused by hydrogen peroxide and menadione, but the virulence of chap1 mutants was unaffected. Upon activation by oxidizing agents or plant signals, a green fluorescent protein (GFP)-CHAP1 fusion protein became localized in the nucleus. Expression of genes encoding antioxidant proteins was induced in the wild type but not in chap1 mutants. Activation of CHAP1 occurred from the earliest stage of plant infection, in conidial germ tubes on the leaf surface, and persisted during infection. Late in the course of infection, after extensive necrotic lesions were formed, GFP-CHAP1 redistributed to the cytosol in hyphae growing on the leaf surface. Localization of CHAP1 to the nucleus may, through changes in the redox state of the cell, provide a mechanism linking extracellular cues to transcriptional regulation during the plant-pathogen interaction.